Punção de fístula arteriovenosa de pacientes em hemodiálise: evidências para a enfermagem - Rodrigues, Jéssica Guimarães (2018)
Hemodialysis is the most common category of kidney replacement therapy set for chronical kidney disease. In order to perform this treatment it’s needed a vascular access (VA) that offers an adequate flow rate, a long use-life and a low rate of complications. The Arteriovenous Fistula (AVF) is the closest access to meet these requirements. It can, however, present complications and, during the cannulation that usually happens three times per week, adverse events (AE) can occur to the patient. The arteriovenous fistula cannulation must happen with safety in order to prevent future patency problems. There are three methods of cannulation: area, rope ladder and buttonhole. In the area method, the insertion points of the needles are in the same area; in the rope ladder method there’s the varying of the place of the puncture, at a distance defined by the previous puncture, all along the VA; and in the buttonhole method, the needle’s insertion happen in the same place, angle and deepness, forming a subcutaneous tunnel that will be cannulated with the blunt needle. Each one of these methods has its own particularity and can influence in the need to repair the fistula. This is a prospective cohort study, during the course of six months, from April to September of 2017, conducted with the participation of 347 patients using the vascular access by autologous arteriovenous fistula, within three hemodialysis clinics in the city of Goiânia - GO. The data collection happened by weekly interview to the patients, using a structured instrument online. The research was approved by the Ethics Committee and the participation conditioned to signing of the consent form by the patient. The general objective was to analyze the factors that can influence in the necessity to repair the arteriovenous fistula of patients in hemodialytic treatment cannulated by different cannulation methods. The specific objective was to relate the adverse events and complications in the different arteriovenous fistula cannulation methods. We’ve found that in the buttonhole method, the most frequent AE was dermatitis and misscannulation, and in the area/rope-ladder methods, the most frequent AE were haematoma and peri-punction bleeding. The patients in the buttonhole method group received the hemodialytic treatment with a higher blood flow compared the other group. We’ve observed that the dual lumen catheter (DLC) is a predictor to the need of AVF repairments, due to enhancing in 28% the risk of need for AFV repair. The “arterial” retrograde cannulation has presented itself as a protection factor, diminishing the need to AVF repairments in 1%. In conclusion, the buttonhole method is recommended, since there is an intermittent surveillance of the arteriovenous fistula by the nurse in the touching exam. The area method is not recommended, and the rope ladder method should be individually evaluated in future studies. The nurse must act by monitoring the AFV, surveillance of the patency parameters and health education to the patients for the AVF self-care, as well as continued education to the nursing team in order to promote safe and scientifically based practices.